Cyclic Oxidation of Fe–18Cr–21Mn–0.65N Austenitic Stainless Steel at 400–700 °C - Kumar S.; Mahobia G.S. (My University, 2025)
Low nickel, nitrogen stabilized austenitic stainless steel has not been explored for its application in the temperature range of 400–700 °C. In the present investigation, nitrogen stabilized austenitic stainless steel (Fe–18Cr–21Mn–0.65 N) was oxidized cyclically from 400 to 700 °C up to 100 h. The effect of moist airflow on oxidation behavior from 400 to 700 °C was systematically studied gravimetrically and the oxidized surfaces were characterized using SEM(EDS) and XRD. Mn diffused from the matrix to surface and reacted with the oxygen associated with the passive chromia layer and formed non-protective Mn2O3 and spinels of the oxides of Fe, Cr and Mn. At 700 °C, there was rapid vaporization of Cr and consequent reduction in weight gain in dynamic air as compared with that in static air. Precipitation of Cr2N of different morphology was established through TEM analysis. © 2020, The Indian Institute of Metals - IIM.